Ask a question

Find the general solution?

Find the general solution of x'=(1, sqrt(3), sqrt(3), -1)x+(e^t, sqrt(3)*e^-t).

(this is 2x2 matrix with 1 and sqrt(3) on the left, sqrt(3) and -1 on the right. And 2x1 matrix with e^t on top, sqrt(3)*e^-t on bottom. I know how to find the answer for 2x2 matrix but not the 2x1 matrix. Please help me step by step. The answer for 2x1 matrix is -(2/3, 1/sqrt(3))e^t+(-1, 2/sqrt(3))e^-t where 2/3 is on the top, 1/sqrt(3) is on bottom, and -1 is on top, 2/sqrt(3) is on bottom.)


1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Andre W. | Friendly tutor for ALL math and physics coursesFriendly tutor for ALL math and physics ...
5.0 5.0 (3 lesson ratings) (3)
Check Marked as Best Answer
You found the homogeneous solution
xh=c1(-1/sqrt(3),1) e-2t +c2 (sqrt(3),1) e2t
To find the inhomogeneous solution you can use one of two methods
A) undetermined coefficients
B) variation of parameters
I will do method A), perhaps somebody else will do method B) for you.
Your inhomogeneous term is (et, sqrt(3)*e-t), which means x MUST be of the form
x= (A1,A2) et + (B1,B2) e-t
We have to find out what A1, A2, B1, and B2 are. We do this by substituting x and its derivative
x'=(A1,A2) et - (B1,B2) e-t
into the original equation,
x'=(1, sqrt(3), sqrt(3), -1)x+(e^t, sqrt(3)*e^-t)
I will do the matrix term first:
(1, sqrt(3), sqrt(3), -1)x = (1, sqrt(3), sqrt(3), -1) ( (A1,A2) et + (B1,B2) e-t)
= ((A1+sqrt(3)A2)et + (B1+sqrt(3)B2)e-t ,  (sqrt(3) A1 -A2)et + (sqrt(3) B1 -B2)e-t )
Therefore, the first component of x' is
A1 et - B1 e-t = (A1+sqrt(3)A2)et + (B1+sqrt(3)B2)e-t +et
The second component of x' is
A2 et - B2 e-t = (sqrt(3) A1 -A2)et + (sqrt(3) B1 -B2)e-t +sqrt(3)*e-t
Let's collect all terms with an et from the first equation and from the second equation:
A1 = A1+sqrt(3)A2 +1
A2 = sqrt(3) A1 -A2
In the first of these, A1 cancels and we get
A2 = -1/sqrt(3).
Plug this into the second equation and get
A1 = -2/3
Now we need to find B1 and B2. For this we collect all terms with an e-t from the first and the second x' equation:
- B1  = B1+sqrt(3)B2
- B2 = sqrt(3) B1 -B2 +sqrt(3)
In the second of these equations, B2 cancels and we get
B1 = -1
Plug this into the first equation and get
B2 = 2/sqrt(3)
Therefore we found
x= (-2/3,-1/sqrt(3)) et + (-1,2/sqrt(3)) e-t
which is your solution!